CERTAIN INVESTIGATION ON CARDIOVASCULAR MONITORING SYSTEM USING INTERNET OF THINGS. - A., DEVIPRIYA; SUJATHA, T.; R., SIVARAMAKRISHNAN; JANANI, R.; BRINDHA, D. (Turkish Journal of Physiotherapy Rehabilitation, 2021)
Recently, humans are lost their life due to respiratory failure. At present in India, the coronary scene passing percentage will be 47%. This happened with a delayed consequence of people eating habit, age factor, turn of events and different parts. The essential driver of death during respiratory disappointment isn't giving hope to the patient. With continually noticing this beat rate & sweat of a patient, respiratory disappointment will be recognized. Aim of the recommendation is used to build up a very high-benefit & insignificant exertion contraption which is used to calculate the amount of beat pounds each patient snapshot & perceiving a cardiovascular failure by placing the sensors on any one of the finger (excluding the thumb) or any point in the human body that the heart beat can be identified or surveyed from, and along these lines demonstrating the output of the persistent screen of the Arduino IDE. In order to provide the performance accuracy of the given system, a sensor will be used to identify the sweat. Suppose any abnormalities occurred, the GSM (Global System for Mobile Communications) module can be impelled & it will send an alarm message to the adaptable device which can be given to Arduino code. The nearest centre of the patient is identified with the Google Maps API then the details are send to the family members. In addition to this, Electronic Health Records (EHR) will be shared to the nearest hospital for tracking or monitoring the patient health history. This implementation performs careful distinctive evidence & track messages. This design will help the people to save their life in a short period of time.